Patrimônio e (é) poder : usos do patrimônio nas revistas do IPHAN de 1937 a 1984 - Lorenzon, Fernando Arnold (2017)
When one hears about patrimony, one usually imagines something about the preservation of monuments of easy visualization and linked to a dominant culture, such as buildings, churches, works of art, etc. These elements usually refer to the immigration that initiated the colonization in specific places and related to the religiosity that predominates in the locality. Another misconception about heritage is that everything that is produced in a given context is part of the national identity, and with the passing of the years and the coming of new generations, new identitary and cultural foundations have sometimes been created Coming from different contexts and periods. The state political movements are the product of specific historical demands, both the creation of policies or actions and the creation of institutions from the most diverse areas. For example, the case of SPHAN (Service of National Historical and Artistic Heritage) That did not follow a different tendency where, besides the Getúlio Vargas government include in its constitution a specific law for the national historical and cultural patrimony, also created an organ whose function was to legitimize a national identity guided by the memory built through the national historical patrimony defined and divulged through the Magazine of the Service of National Historical and Artistic Patrimony. This dissertation aims to analyze the National Historic and Artistic Patrimony Journals, published by SPHAN (Service of National Historical and Artistic Patrimony) between the years of 1937 and 1984 seeking to highlight the meanings given to patrimony, as well as to investigate how The magazine and the institution through it were related to the nationalist policies of the governments of President Getúlio Vargas (Estado Novo) and the military period. For this, we seek to demonstrate, through the publications and discourse analysis produced on equity and subjects connected to it, which national identity was built by the ideals of heritage that influenced the development of the journal and were released by the same.